Issues and Concerns of Teachers Towards Modular Distance Learning Approach (International Journal of Scientific Research and Management (IJSRM), 2023)
This research investigated the teachers’ issues and concerns towards modular distance learning approach. This study aimed to determine the level of issues and concerns encountered by teachers in the implementation of modular distance learning approach and the significant difference in the level of issues and concerns of teachers towards modular distance learning approach when grouped according to sex, number of years in service and number of related trainings. The study employed quantitative research, specifically a descriptive research design to determine the issues and concerns of fifty (50) elementary teachers of Cadiz District II in the Schools Division of Cadiz City. Total Purposive Enumeration sampling was used in selecting the respondents for the target samples. They were grouped according to the schools they are stationed at. The statistical tools used for the treatment of data were mean and standard deviation for problems 1 and 2, Independent t-test, and One-Way ANOVA used for problems 3 and 4. The results revealed that the teachers have high level of issues and concerns encountered towards modular distance learning approach. Moreover, the result of this investigation suggested that females have higher competencies on the level of issues and concerns of teachers towards modular distance approach than males. Therefore, the null hypothesis is rejected as a significant difference exists in the issues and concerns of teachers towards Modular Distance Learning approach when grouped according to sex. On the other hand, the null hypothesis is accepted as no significant difference exists in the issues and concerns of teachers towards Modular Distance Learning approach when grouped according to number of years in service and number of related trainings.